A Forward-Looking Macroeconomic Simulation Model for a Developing Country. (IMF Working Papers; Working Paper ;, 1989)
The paper develops a small dynamic macroeconomic simulation model for a representative developing country which relies on familiar macroeconomic theory and in which expectations are formed rationally. The model is useful for the analysis and simulation of important policy questions in a general-equilibrium setting. Several policy experiments are conducted which illustrate the workings of the model and yield fresh insights into the effects of standard macroeconomic policies in developing countries.